Step-by-step explanation:
We do the brackets first, following BODMAS rules
so, 4× 5x ÷ 5y = 1xy.
= 4 × 1xy
= 4xy.
I guess that's the answer.
Example Of:-
<u>Sum:</u>
<em>2</em><em>x</em><em> </em><em>+</em><em> </em><em>7</em><em>y</em>
<u>term:</u><u> </u>
<em>5x + 7 = 5x and 7 are terms. </em>
<u>product</u><u>:</u>
<em>2a × 3b </em>
<u>factor:</u><u> </u>
<em>always </em><em>remember</em><em>,</em><em> </em><em>a </em><em>number </em><em>is </em><em>a </em><em>factor </em><em>of </em><em>itself.</em>
<em>5</em><em>x</em><em> </em><em>+</em><em> </em><em>7</em><em>y</em>
<em>factors </em><em>=</em><em> </em><em> </em><em>5</em><em> </em><em>+</em><em> </em><em>x</em><em> </em><em>+</em><em> </em><em>5</em><em>x</em><em> </em><em>+</em><em> </em><em>7</em><em> </em><em>+</em><em> </em><em>y </em><em>+</em><em> </em><em>7</em><em>y</em><em>.</em>
<u>Quotient:</u><u> </u>
<em> </em><em>1</em><em>0</em><em>d</em><em> </em><em>÷</em><em> </em><em>5</em><em>j</em><em> </em><em>=</em><em> </em><em>2</em><em>d</em><em>j</em><em> </em>
<u>coefficient</u><u>:</u><u> </u>
<em>In the number 3x, </em><em>3</em><em> </em><em>is </em><em>the </em><em>coefficient</em><em> </em><em>of </em><em>x.</em><em> </em>
<em>but,</em><em> </em><em>in </em><em>the </em><em>number </em><em>x </em><em>(</em><em>raise </em><em>to)</em><em> </em><em>2</em><em>,</em><em> </em><em>the </em><em>coefficient</em><em> </em><em>is </em><em>1</em><em>.</em><em> </em>
<em>
</em>
<h3 />
Answer:
$8 for 3 pounds
cost for p pounds: 3.50p - 2.50
Step-by-step explanation:
Cost of 3 pounds:
Original cost = Cost per pound x 3
= 3.50 x 3
= 10.50
Coupon = 2.50
Final cost = Original cost - Coupon
= 10.50 - 2.50
= $8
Cost of p pounds:
Original cost = Cost per pound x p
= 3.50 x p
= 3.50p
Coupon = 2.50
Final Cost = Original Cost - Coupon
= 3.50p - 2.50
First, distribute the 2.
2x+6=6+2x
These are the same, so therefore it is infinitely many, because whatever you plug in for x will work.
Answer:
y=-5/2x-1
Step-by-step explanation:
first find the gradient whereas since the two lines are parallel they hav the same gradient. y=mx+c whereas m is the gradient. 5x+2y=12
2y=-5x+12
y=-5/2x+12(so the gradient is -5/2x..... <u>g</u><u>r</u><u>a</u><u>d</u><u>i</u><u>e</u><u>n</u><u>t</u><u>=</u><u>-</u><u>5</u><u>/</u><u>2</u>
<u>y</u><u>-</u><u>4</u>=-5/2
x+2
y-4=-5/2(x+2)
y-4=-5/2x-5
y=-5/2x-5+4
y=-5/2x-1
Answer:
10 ft 10 in
Step-by-step explanation:
Note that there are 12 inch in 1 feet. Add corresponding numbers together:
6 ft 2 in + 4 ft 8 in = (6 ft + 4 ft) + (2 in + 8 in) = 10 ft + 10 in
10 ft 10 in is your answer.
~